2016
DOI: 10.1108/bepam-06-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Disaster risk reduction infrastructure requirements for South-Western Bangladesh

Abstract: Purpose Development of effective disaster risk reduction (DRR) strategies for communities at risk of being affected by natural disasters is considered essential, especially in the wake of devastating disaster events reported worldwide. As part of a wider research study investigating community perspectives on existing and potential strategies for enhancing resilience to natural disasters, community perspectives on infrastructure and structural protection requirements were investigated. The paper aims to discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…23 While comprehensive DRR initiatives should not be confined to infrastructure alone, they should cover a wide range of issues, such as representing the schools of thought in science, engineering, structural, and physical organization, since infrastructure plays an important role in reducing vulnerability of risky communities, such as schools. 24 This is particularly important for developing countries such as Indonesia, where the ability of communities to implement DRR is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…23 While comprehensive DRR initiatives should not be confined to infrastructure alone, they should cover a wide range of issues, such as representing the schools of thought in science, engineering, structural, and physical organization, since infrastructure plays an important role in reducing vulnerability of risky communities, such as schools. 24 This is particularly important for developing countries such as Indonesia, where the ability of communities to implement DRR is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…According to study respondents, training programs to increase stakeholder capabilities in disaster risk reduction issues should be well supported with funds and other resources; funding constraints do not motivate the stakeholders and communities to take disaster prevention measures. Previous research also showed that lack of financial resources significantly hinders the ability to better prepare for future hazards, for instance, by moving out of vulnerable areas and making homes safer (Wedawatta et al 2016 ). The respondents’ opinions were that such training programs should be carried out regularly.…”
Section: Resultsmentioning
confidence: 99%
“…According to (Haifani, 2008) Information media has a significant influence on students' preparedness in disaster risk reduction. Integrating information media such as the internet, tv and radio into learning in schools may help alter attitude (Wedawatta et al, 2016) (Lebe et al, 2014). Radio, tv and the internet are propaganda media with wide and inexpensive dissemination of information that will potentially influence students to conduct discussions (Suprajitno, 2017).…”
Section: Discussionmentioning
confidence: 99%